Mencari Pemimpin Negarawan Membagun Demokrasi Berkeadaban Dan Dinamika Pemilihan Umum Presiden 2024 Menuju Indonesia Emas - Hadi Karyono; Krismiyarsi Krismiyarsi (Kertha Wicaksana, 2023)
Besides having been ordered by God Almighty, the statesman leader was also not formed immediately. A statesman leader will always place professionalism and morals as the main standard. Leaders of statesmen whose policies depart from the collective interests of the people and minimize the domination of collegial interests originating from the group interested sts and encouragement. Leaders of statesmen never mathe ke empty promises. If you promise, the promithe se is a debt that will be accounted for vertically and horizontally. General elections are one of the vehicles for democracy as a manifestation of people's sovereignty. From the above expectations, we should be able to build a civilized democracy, a naresearchocracy that brings goodness and dignity and welfare to society (welfare state), far from SARA intrigues or identity politics. The role of the younger generation as the future leadership relay must be positioned, seated, and understood about future statesman leadersingle-spacedf 11-pointl parties is not only to produce a political leader but also to be able to produce a statesman leader.